Effect of the complex improver on consumer properties of bakery products - Bilyk, Olena; Halykova, Esma; Shevchenko, Anastasiia; Kochubei-Lytvynenko, Oksana; Bondarenko, Yuliia; Fain, Albina (My University, 2020)
A study was conducted on the possibility of using a directional baking improver "Freshness +". The consumer properties of the bakery product "Freshness" (from premium wheat flour, yeast, salt, margarine, white sugar) were investigated. The use of improver in amount of increases the specific volume of products, improves form resistance, porosity and reduces the fermentation time. The use of the im-prover also slows down the starch retrograde.
Keywords: complex improver; consumer properties; bakery products; quality; properties; кафедра технології хлібопекарських і кондитерських виробів; кафедра експертизи харчових продуктів; кафедра технології молока і молочних продуктів